Mirage simulations of the massiv sample. Issue Volume 10:Issue S309(2014) (9th February 2015) - Amram, P.; Perret, V.; Epinat, B.; Bournaud, F.; Contini, T.; Divoy, C.; Garilli, B.; Kissler-Patig, M.; Le Fevre, O.; Lopez-Sanjuan, C.; Moultaka, J.; Pairo, L.; et al.
Abstract : The MIRAGE sample (Merging & isolated high-redshift AMR galaxies; Perret 2014, PhD dissertation; Perret et al . 2014, AA 562, 1) has been built in order to understand the contribution of the merger processes to the mass assembly in the MASSIV (Mass Assembly Survey with SINFONI in VVDS, Contini et al . 2012, AA 539, 91) sample. It consists of a sample of idealized simulations based on the RAMSES code; the initial conditions were designed to reproduce the physical properties of the most gas-rich young galaxies. The sample is composed of 20 simulations of mergers exploring the initial parameters of mass and orientation of the disks with a spatial resolution reaching 7 parsecs.